OPTIMASI PROSES DESTILASI UAP ESSENTIAL OIL - Zuhdi Ma'sum; Wahyu Diah Proborini (Universitas Tribhuwana Tunggadewi Malang, 2016)
Most of essential oils are produced using simple method steam destillation. The tool used in this reseach were made by a small workshop. This equipment can be used for distillation and condensation. But the best process that can be applied to this equipment is still unknow. The purpose of this study is to obtain the shortest processing time and optimization of production processes. This condition is achieved by decrease the rate of increasing temperature of cooling water. With the achievement of this conditions, the optimization of the essential oil distillation process in oil refining production system can be determined. The method used in this research is to reduce the temperature of the water out of the condenser using cooling tower.The best temperature decrease is obtained at A process with the difference in temperature of the cooling water at 1.5oC, 2.5oC, 3.5oC, 5.5oC. The decrease of increasing temperature of the cooling water can increase the capacity process through the addition of process. Optimization of processing time in 12 hours resulted repetition of the process at 4 hour by 3 times. With the cooling tower can reduce the rate of increase temperature in cooling water.Yield of Essential oils increase 29%.